CEOs' hometown connections and stock price crash risk: Evidence from emerging market - Fanjie Fu; Shujie Yao; Jing Fang; Yu Zheng; Zongdi Toby Wang (Borsa İstanbul Review, 2022)
This paper investigates the impact on the risk of a crash in the stock price (SPCR) of a hometown connection between a firm's chief executive officer (CEO) and suppliers. Using manually collected data on CEOs' hometown connections among Chinese A-share companies (A-shares, or RMB common shares, are issued by companies registered in China and only listed in China) listed on the Shanghai and Shenzhen Stock Exchanges, we find that these connections significantly raise SPCR. Hometown connections do not guarantee managerial ethics. On the contrary, CEOs might abuse the trust and reputation from a hometown connection. We propose plausible explanations for the 'hometown effect': CEO personal interests and overconfidence. The hometown effect is more pronounced among CEOs at state-owned enterprises, firms with low CEO compensation, local CEOs, low-quality auditing, and in areas with low marketization. We reveal that CEO shareholding strengthens the hometown effect. The research findings of this paper have significant implications for investors with respect to SPCR, as they make decisions about various listed firms with knowledge about of CEO hometown connection.
Keywords: G17; G30; M12; 330; CEOs' hometown connections; Informal institutions; Information asymmetry; Trust of outsiders; Stock price crash risk